Two new species of Euphorbia sect. Nummulariopsis (Euphorbiaceae) from South America - Pablo Carrillo-Reyes; Victor W. Steinmann (Anales del Jardín Botánico de Madrid, 2011)
Two new species of sect. Nummulariopsis, Euphorbia guaraniorum and E. cordeiroae, are described and illustrated. Euphorbia guaraniorum appears to be related to E. portulacoides and is distinguished by its densely arranged ensiform leaves. It is known only from the Yacyretá and Ybycui Islands in southern Paraguay. Euphorbia cordeiroae, occurs in the state of Goiás, Brazil, and is similar to E. stenophylla, from which it differs in its higher stature and very narrow and loosely arranged leaves.